Sol-gel Eu3+/Tm3+ doped transparent glass-ceramic waveguides - Ribeiro, SJL; Araujo, C. C.; Bueno, L. A.; Goncalves, R. R.; Messaddeq, Younes [UNESP] (Elsevier B.V., 2004)
Eu3+ and Tm3+ doped lanthanum fluoride and lanthanum oxyfluoride are obtained from Eu3+, Tm3+ containing lanthanum fluoracetate solutions. The nature of the crystal phase obtained could be controlled by the temperature of heat treatment. Spectral characteristics of Eu3+ doped crystal phases were sufficiently different to allow utilization of Eu3+ as structural probes. Tm3+ emission at the technologically important spectral region of 1450nm could be observed for the fluoride and oxyfluoride crystal phases. The large bandwidth obtained (around 120nm) suggests potential applications in optical amplification. SiO2-LaF3-LaOF composite materials were also prepared. It is observed that for heat treatments above 800degreesC, fluorine loss, probably in the form of SiF4 hinder the observation of Tm3+ emission. Eu3+ spectroscopic characteristics clearly show the evolution of a fluoride like environment to an amorphous oxide one as the temperature of heat treatment increased. Thin films obtained by dip-coating on V-SiO2 substrates and treated at 300degreesC, 500degreesC and 800degreesC display guided modes in the visible and infrared regions. Optical characteristics (refractive index and films thickness) were obtained at 543.5, 632.8 and 1550nm. Attenuation as low as 1.8dB/cm was measured at 632.8nm. (C) 2004 Published by Elsevier B.V.